Effects of an antioxidant on the shear bond strengths of orthodontic brackets after conventional and laser-assisted extra-coronal bleaching = Efecto de un antioxidante sobre la fuerza de unión de brackets de ortodoncia posterior al blanqueamiento convencional y asistido por láser - Fundaoĝlu Küçükekenci, Funda; Serkan Küçükekenci, Ahmet; Kutalmiş Büyük, Süleyman (2018)
Purpose: The purpose of this study was to evaluate the effects of the application of antioxidant on the shear bond strengths (SBS) of orthodontic brackets bonded to human enamel after extra-coronal bleaching with hydrogen peroxide (HP). Materials and methods: Fifty freshly extracted premolars were randomly divided into three groups. One group (Group 1) was bleached with 40% HP (n=20), another group (Group 2) was bleached with 40% HP and activated with an Nd: YAG laser (n=20), and a control group (Group 3) received no treatment (n=10). After the bleaching procedure, Groups 1 and 2 were further divided into two subgroups (Group 1a, Group 1b, Group 2a, and Group 2b). Specimens in Groups 1a and 2a (n=10) received no antioxidant application. A 10% sodium ascorbate solution was applied to specimens in Groups 1b and 2b (n=10). The brackets were then bonded with light-cure adhesive paste to the enamel surfaces of all experimental groups. Specimens were subjected to SBS tests for debonding. Results: The SBS of brackets bonded in Groups 1 and 2 were significantly lower than those of brackets bonded to the control group (p<0.001); however, no statistically significant differences in SBS were noted in Groups 1 and 2 (p>0.001). The antioxidant-treated SBS of brackets in Groups 1b and 2b were significantly higher than those of Groups 1a and 2a (p<0.001). Conclusions: The application of 40% HP had a negative effect on the bond strength. The use of antioxidant for 15 min resulted in the reversal of failed bond strength.
El objetivo del presente estudio fue evaluar los efectos de la aplicación de un antioxidante sobre las fuerzas de unión (SBS) de brackets de ortodoncia posterior al blanqueamiento con peróxido de hidrógeno (HP). Metodología: Cincuenta premolares recién extraídos se dividieron aleatoriamente en tres grupos. El Grupo 1 se trató con 40% de HP (n=20), el grupo 2 con 40% de HP y se activó con láser de Nd: YAG (n=20) y un grupo de control (Grupo 3) no recibió tratamiento (n=10). Después del blanqueamiento, los Grupos 1 y 2 se dividieron en dos subgrupos (Grupo 1a, Grupo 1b, Grupo 2a y Grupo 2b). Las muestras en los subgrupos 1a y 2a (n=10) no recibieron ninguna aplicación del antioxidante. Se aplicó una solución de ascorbato de sodio al 10% a las muestras en los Grupos 1b y 2b (n=10). Luego, los brackets se adherieron a las superficies de esmalte de todos los grupos experimentales. Las muestras se sometieron a pruebas de SBS y los datos analizados estadisticamente. Resultados: La fuerza de unión de los grupos 1 y 2 fue significativamente más baja que el grupo de control (p <0.001); sin embargo, no se observaron diferencias estadísticamente significativas en SBS entre los grupos 1 y 2 (p>0.001). Las muestras tratadas con antioxidantes de los grupos 1b y 2b fueron significativamente mayores que las de los grupos 1a y 2a (p <0,001). Conclusion: La aplicación de 40% HP tuvo un efecto negativo en la resistencia de unión de los brackets. El uso de antioxidante durante 15 minutos mejoró significativamente la SBS.
En revista Odóvtos, vol. 20, no. 3 (septiembre-diciembre 2018)
Descripción basada en el contenido visto 01 de agosto, 2024
También disponible en formato HTML
Keywords: ORTODONCIA; ANTIOXIDANTES -- EVALUACION - PRUEBAS; RECUBRIMIENTO DENTAL ADHESIVO; BLANQUEO DE LOS DIENTES; LASERS EN MEDICINA